Rozwój i cechy bezrobocia na Dolnym Śląsku według powiatów o zróżnicowanej strukturze społeczno-gospodarczej - Kociszewski, Jerzy; Krzemień, Robert (Growth of Unemployment and Its Characteristics in Lower Silesia According to Administrative District with Different Socio-Economic Structure, 2008)
Economic transformation goes with the restructuring of labour market manifested by wide labour resources demobilization, employment reduction and unemployment growth. It is influenced by national enterprises privatization, private sector development and market mechanism adjusting supply and demand of labour. Ups and downs in the labour market in Poland and in the region show cyclical nature - described as transitional. At the same time, the unemployment structure is evolving in the aspect of sex, age, education, unemployment durability and its spread among regions as well as the local scale. The significant factor sustaining the situation is socio-economic structure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 282-296